One-year outcome of combination therapy with intravitreal aflibercept and photodynamic therapy for polypoidal choroidal vasculopathy - Hsin-Yu Weng; Tzu-Lun Huang; Pei-Yao Chang; Jia-Kang Wang (BMC, 2019)
Abstract Background To investigate the one-year visual and anatomical outcomes of combination therapy with intravitreal aflibercept (IVA) and photodynamic therapy (PDT) for treating polypoidal choroidal vasculopathy (PCV). Methods This was a retrospective case-series study, including 30 eyes from 30 patients with treatment-naïve PCV treated by combination therapy with IVA and PDT. Best-corrected visual acuity (BCVA), central retinal thickness (CRT), complete polyp regression rate, and dry macula rate were recorded every 3 months during 12-month follow-up. Clinical factors associated with final visual outcome and retreatment were investigated. Results The mean LogMAR BCVA was significantly improved from 0.73 ± 0.65 at baseline to 0.51 ± 0.60 (p = 0.01), and the mean CRT was also significantly improved from 339 ± 96 μm at baseline to 244 ± 43 μm at 12-month follow-up (p <  0.001). Complete regression of polypoidal lesions was 76.7%, and dry macula rate was 100% at 12 months. Better final BCVA was associated with younger age and better baseline BCVA (p = 0.02 and p <  0 001). The patients without complete polyp regression at 3-month follow-up were associated with retreatment (p = 0.03). Conclusion In this study, combination therapy with IVA and PDT had significant visual and anatomical improvements to PCV patients during one-year follow-up. Better baseline BCVA and younger age were found to be associated with better visual outcome.